A New Topology for Speed control of Sensor less BLDC Motor with Reduced Commutator Switches and Improved Input Power Factor (International Journal of Engineering and Computer Science, 2014)
The Brushless Direct Current (BLDC) motors are one of the motor types rapidly gaining popularity. BLDC motors are used in aerospace applications, medical field, industrial automation equipment and instrumentation. As the name implies, BLDC motors do not use brushes for commutation; instead, they are electronically commutated. This paper proposes a new optimized  drive for speed control of BLDC motor, In this operation mode, it approximates a voltage follower and the line current follows the line voltage waveform to a certain extent. The reduction in low-order harmonics and improved power factor is achieved without the use of any voltage or current sensors. The simplicity and reduced parts count of the proposed topology make it an attractive low-cost choice for many variable speed drive applications.